Respuesta :

Answer:

-3

Step-by-step explanation:

Remember the following:

cos(x)=cos(x/2 + x/2) = cos(x/2)*cos(x/2) -sin(x/2)*sin(x/2)

cos(x)=cos2(x/2) - sin2(x/2)

We also know that sin2(a)+cos2(a)=1,

so sin2(x/2)=1 - cos2(x/2). obtained from previous step.

So, our first expression can be written as:

cos(x)=cos2(x/2)-1+cos2(x/2)

Where we obtain that: cos(x/2)= sqrt( 1+ cos(x))/ sqrt(2)

If we again use sin2(a)+cos2(a)=1, we will obtain the following relation:

sin(x/2)= sqrt(1-cos(x))/sqrt(2)

Next Tang(x/2)= sin(x/2) / cos(x/2)= sqrt(1-cos(x))/sqrt(1+cos(x))=

SQRT(9/1)=3

In the given range, cos(x), hence tan(x/2) is also negative